Swainsonine-induced vacuolar degeneration is regulated by mTOR-mediated autophagy in HT22 cells. (15th January 2023) - Liu, Yanbing; Zhang, Shuhang; Wang, Weina; Tang, Shiyu; Zhu, Yiru; Wang, Meng; Cao, Bingqian; Zhu, Yanli; Tang, Lihui; Liu, Yiling; Mo, Chonghui; Zhao, Baoyu; et al.
Abstract: The indolizidine alkaloid, swainsonine (SW), is the main toxic component of locoweed, which can cause locoism in animals with characteristic neurological dysfunction. Pathological manifestations at cellular level include extensive vacuolar degeneration. Studies have shown that SW can induces autophagy, but the role and mechanism of autophagy in SW-induced vacuolar degeneration is unclear. In this study, we analyzed the role of autophagy in SW-induced cell injury in mouse hippocampal neurons cell line (HT22) using western blotting, qRT-PCR, transmission electron microscopy and immunofluorescence microscopy. The results showed that the expressions of LC3-II, ATG5, Beclin1 and p62 proteins and their mRNAs in HT22 cells were induced by SW treatment. The SW treatment increased the number of autophagosomes with enhanced fluorescence intensity of monodansylcadaverine (MDC) and LC3-II in a time-dose dependent manner. The results of lysosome staining showed that SW could increase the number of lysosomes, increase the intraluminal pH. Transmission electron microscopy results indicate that SW induced autophagosomes, and Baf A1 could effectively alleviate SW-induced vacuolar degeneration. At the molecular level, SW treatment inhibited the expression of p-PI3K, p-AKT, p-ERK, p-AMPK, p-mTOR, p-p70S6K and p-4EBP1 and promoted the expression of p53. Our results collectively suggest, PI3K/AKT/mTOR, ERK/mTOR and p53/mTOR signaling pathways are involved in the regulation of SW-induced autophagy in HT22 cells, while the AMPK/mTOR signaling pathway is not involved in this regulation. Inhibition of autophagic degradation can effectively alleviate SW-induced vacuolar degeneration. Graphical Abstract: ga1 Highlights: SW can induce autophagy, impair lysosomal function, and cause autophagy degradation disorder. Baf A1 can alleviate vacuolar degeneration caused by SW and restore the decreased expression levels of Man2a1 and Man2b1 . PI3K/AKT, ERK and p53 signaling pathways are involved in the regulation of SW-induced autophagy, except for AMPK/mTOR.